2009
DOI: 10.1007/s12195-009-0073-7
|View full text |Cite
|
Sign up to set email alerts
|

Stretch and Shear Interactions Affect Intercellular Junction Protein Expression and Turnover in Endothelial Cells

Abstract: Complex hemodynamics play a role in the localization and development of atherosclerosis. Endothelial cells (ECs) lining blood vessel walls are directly influenced by various hemodynamic forces: simultaneous wall shear stress (WSS), normal stress, and circumferential stress/strain (CS) due to pulsatile flow, pressure, and diameter changes. ECs sense and transduce these forces into biomolecular responses that may affect intercellular junctions. In this study, a hemodynamic simulator was used to investigate the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 55 publications
(88 reference statements)
0
20
0
Order By: Relevance
“…Leader cells have been observed in collective migration during cancer cell invasion, vascular sprouting, wound closure, and embryogenesis (36,37). Furthermore, there is some evidence that mechanical forces can modulate coordinated migration in vascular morphogenesis: It has been shown that forces exerted by flowing fluids can induce changes in endothelial junction structure (38), differentiation of vascular wall cells (39), and tip cell formation (40). Interestingly, our leader cells are morphologically and functionally similar to endothelial tip cells.…”
Section: Discussionmentioning
confidence: 68%
“…Leader cells have been observed in collective migration during cancer cell invasion, vascular sprouting, wound closure, and embryogenesis (36,37). Furthermore, there is some evidence that mechanical forces can modulate coordinated migration in vascular morphogenesis: It has been shown that forces exerted by flowing fluids can induce changes in endothelial junction structure (38), differentiation of vascular wall cells (39), and tip cell formation (40). Interestingly, our leader cells are morphologically and functionally similar to endothelial tip cells.…”
Section: Discussionmentioning
confidence: 68%
“…Several reports have provided evidence of flow shear stress-mediated distribution of tight junction proteins, in which exposure to shear stress leads to a transient decrease (<4 hrs post shear) in VE-cadherin or occludin protein expression, as endothelial cells migrate and align in the direction of flow. 14,15,39,[55][56][57][58][59] Studies investigating the effect of shear stress on permeability of macromolecules across the endothelium also revealed that endothelial permeability is acutely sensitive to shear stress in vitro. 53 Exposure of both 1 and 10 dyne/cm 2 dramatically increased permeability of FITC-BSA after 30 and 60 minutes; however, permeability returned to pre-shear values after 120 minutes.…”
Section: Endothelial Barrier Functionmentioning
confidence: 99%
“…The temporal phase angle between flow and pressure generated by wave reflection in the circulation and the inertial effects of blood flow cause time lags to occur between WSS and WCS. The temporal phase angle between WSS and WCS has been referred to as the stress phase angle (SPA) (Qin et al, 2006;Berardi and Tarbell, 2009). Studies have shown that the production rates of the vasoactive agents Nitric Oxide (NO); Prostacyclin (PGI2) and Endothelin-1 (ET-1) of ECs synergistically exposed to WCS and WSS are dependent on the SPA.…”
Section: Introductionmentioning
confidence: 99%
“…In another in vitro study Qiu and Tarbell (2000) found that the highly negative SPA ( À 100 1 compared to À151) suppressed NO and PGI2 and induced ET-1 production. Further in-vitro studies have also shown that a SPA¼ À1801 for asynchronous hemodynamic condition in comparison to a SPA¼01 for synchronous hemodynamic condition represents a strong decrease in NO and PGI2 production, an increase in ET-1 production (Dancu et.al., 2004), a high rate of cell turnover and an increase in the number of leaky junctions (Berardi and Tarbell, 2009). The leaky junctions' increase causes the resistance of the leaky junction pathway to decrease the flow considerably and so the blood plasma flux through the leaky junctions increases.…”
Section: Introductionmentioning
confidence: 99%